Power Dynamics In Negotiation - Kim, Peter H.; Pinkley, Robin L.; Fragale, Alison R. (Academy of Management Review, 2005)
Power is widely acknowledged to affect negotiator performance. Yet few efforts have been made to integrate the most prominent theories of power into a cohesive framework that can account for the results from a broad array of negotiation-relevant research. We address this limitation by proposing a dynamic integrative model that decouples power into four components: (1) potential power, (2) perceived power, (3) power tactics, and (4) realized power. Implications, propositions, and future directions are discussed.